KAJIAN KENDALA EKSEKUSI PIDANA BERDASARKAN SEMA NOMOR 1 TAHUN 2011 DENGAN PASAL 270 KUHAP - Rafi'ah Nafida Zalna; Ismawati Septiningsih (Verstek, 2022)
This article aims to determine the constraints and legitimacy of prosecutors in carrying out criminal executions based on the provisions of the Supreme Court Circular Letter Number 1 of 2011 in terms of the provisions of the Criminal Procedure Code and legal certainty. This type of legal research is normative research with primary and secondary legal materials using a statute approach and a conceptual approach. The technique of collecting legal materials uses library research and the technique of analyzing legal materials is deductive in nature using the syllogism method. As for the results of this study, it was found that based on Article 79 of the Supreme Court Law and Article 7, 8 paragraph of Law Number 11 of 2011 Supreme Court Circular Letter Number 1 of 2011 is not a statutory regulation, but a policy regulation that only has the power internal binding. As a result, SEMA No. 1 of 2011 by the Prosecutor in the criminal procedural law environment is a form of customary law (customary law) which also has legal certainty because the execution must be carried out against a judge's decision that has permanent legal force (in kracht van gewisjde) and has executive power. So that the execution of a crime using the excerpt of the decision certainly has legal certainty for the convict in assisting the convict to immediately obtain the convict's rights while serving his sentence as an inmate in a penitentiary.Keywords: Criminal Execution; Prosecutor's Constraints, Supreme Court Circular Letter (SEMA), Excerpt of the Decision